SISTEM MONITORING DAYA PADA PENGOPERASIAN MOTOR LISTRIK BERBASIS POWER METER - Yahya, Sudirman; Suyadi, Andri; Febriani, Alda (JURNAL TELISKA, 2025)
In the industrial sector, 3-phase induction electric motors are widely used as drivers for conveyors, blowers, elevators, and others. Using an induction motor has many advantages, including relatively cheap prices, easy maintenance, and simple construction. When using a 3-phase induction electric motor, electrical power is an important parameter that needs to be considered. Poor power quality can cause a variety of problems, including reduced efficiency, equipment damage and disruption to the electrical system. Therefore, power monitoring is important to identify possible problems and take appropriate corrective or preventive action. Power monitoring can also provide a better understanding of how power quality can affect the operating efficiency and reliability of 3-phase induction electric motors. This can also be valuable knowledge on understanding and optimizing the performance of 3-phase induction electricity in industrial electrical installation practices by using a Power Meter to monitor the power consumed by the electric motor in real time.